![Slide2.JPG](https://cdn.teachoo.com/d10dd4e2-ffac-4c41-ac96-49cedee38193/slide2.jpg)
![Slide3.JPG](https://cdn.teachoo.com/de7b93b7-fa34-467e-b5af-8f627ac1b36e/slide3.jpg)
![Slide4.JPG](https://cdn.teachoo.com/771fd70d-225a-4cd1-83ad-a6b910563e57/slide4.jpg)
![Slide5.JPG](https://cdn.teachoo.com/162a0bfd-7f8e-487d-88d9-ca7600c9e698/slide5.jpg)
![Slide6.JPG](https://cdn.teachoo.com/83771b7f-34ec-4e08-94d2-21fe6a8caa30/slide6.jpg)
![Slide7.JPG](https://cdn.teachoo.com/fc2255ff-90a9-467e-abac-9b9129511f03/slide7.jpg)
Examples
Last updated at Dec. 16, 2024 by Teachoo
Example 10 Find the following integrals: (ii) โซ1โ(๐ฅ + 3)/โ(5 โ 4๐ฅ โ ๐ฅ^2 ) ๐๐ฅ We can write numerator as ๐ฅ+3= A๐/๐๐ฅ [โ๐ฅ^2โ4๐ฅ+5]+ B ๐ฅ+3= A[โ2๐ฅโ4]+ B ๐ฅ+3=โ2๐ด๐ฅโ4A+B Finding A & B Comparing coefficient of ๐ฅ ๐ฅ=โ2๐ด๐ฅ 1 =โ2A A=(โ1)/( 2) Comparing constant term 3=โ4A+B 3=โ4((โ1)/( 2))+B 3=2+B B=3โ2=1 Now, we know that ๐ฅ+3=A[โ2๐ฅโ4]+B ๐ฅ+3=(โ1)/( 2) [โ2๐ฅโ4]+1 Now, our equation is โซ1โ(๐ฅ+3)/โ(5 โ 4๐ฅ + ๐ฅ^2 ).๐๐ฅ=โซ1โ(1/2 [โ2๐ฅ โ 4]+1)/โ(5 โ 4๐ฅ โ ๐ฅ^2 ).๐๐ฅ =โซ1โ((โ1)/2 [โ2๐ฅ โ 4]+1)/โ(5 โ 4๐ฅ + ๐ฅ^2 ) ๐๐ฅ+โซ1โ1/โ(5 โ 4๐ฅ โ ๐ฅ^2 ) ๐๐ฅ =(โ1)/2 โซ1โ(โ2๐ฅ โ 4)/โ(5 โ 4๐ฅ + ๐ฅ^2 ) ๐๐ฅ+โซ1โ1/โ(5 โ 4๐ฅ โ ๐ฅ^2 ) ๐๐ฅ Solving I1 I1 = (โ1)/2 โซ1โใ(โ2๐ฅ โ 4)/โ(โ๐ฅ^2 โ 4๐ฅ + 5).๐๐ฅใ Let t = โ๐ฅ^2 โ 4๐ฅ + 5 Differentiating both sides w.r.t. ๐ฅ โ2๐ฅ โ 4 =๐๐ก/๐๐ฅ ๐๐ฅ=๐๐ก/(โ 2๐ฅ โ 4) Now, I1 = (โ1)/( 2) โซ1โใ(โ2๐ฅ โ 4)/โ(โ๐ฅ^2 โ 4๐ฅ + 5).๐๐ฅใ Putting the values of (โ๐ฅ^2โ4๐ฅ+5) and ๐๐ฅ I1 = (โ1)/( 2) โซ1โใ(โ2๐ฅ โ 4)/โ๐ก.๐๐ก/((โ2๐ฅ โ4) )ใ I1 = (โ1)/( 2) โซ1โใ1/โ๐ก.๐๐กใ I1 = (โ1)/( 2) โซ1โใ1/(๐ก)^(1/2) .๐๐กใ I1 = (โ1)/( 2) โซ1โใ(๐ก)^((โ1)/2) ๐๐กใ I1 = (โ1)/( 2) ๐ก^((โ1)/( 2) + 1)/(((โ1)/( 2) + 1) )+๐ถ1 I1 = (โ1)/( 2) ๐ก^(1/( 2) )/((1/2) )+๐ถ1 I1 = โ ๐ก^(1/( 2) )+๐ถ1 I1 = โโ๐ก+๐ถ1 Putting back ๐ก=๐ฅ^2โ4๐ฅ+5) I1 = โโ(โ๐ฅ^2โ4๐ฅ+5)+๐ถ1 Solving ๐ฐ๐ I2 = โซ1โใ1/โ(5 โ 4๐ฅ โ ๐ฅ^2 ).๐๐ฅใ I2 = โซ1โใ1/โ(โ(๐ฅ^2 + 4๐ฅ โ 5) ) ๐๐ฅใ I2 = โซ1โใ1/โ(โ[๐ฅ^2 + 2(2)(๐ฅ) โ 5] ) ๐๐ฅใ I2 = โซ1โใ1/โ(โ[๐ฅ^2 + 2(2)(๐ฅ) + (2)^2 โ (2)^2 โ 5] ) ๐๐ฅใ I2 = โซ1โใ1/โ(โ[(๐ฅ + 2)^2 โ 4 โ 5] ) ๐๐ฅใ I2 = โซ1โใ1/โ(โ[(๐ฅ + 2)^2 โ 9] ) ๐๐ฅใ I2 = โซ1โใ1/โ(9 โ (๐ฅ + 2)^2 ) ๐๐ฅใ I2 = โซ1โใ1/โ((3)^2 โ (๐ฅ + 2)^2 ) ๐๐ฅใ It is of form โซ1โใ1/โ(๐^2 โ ๐ฅ^2 ).๐๐ฅ=ใ๐ ๐๐ใ^(โ1)โกใ๐ฅ/๐+๐ถ2ใ ใ Replacing ๐ฅ by (๐ฅ+2) and a by 3, we get I2 = sin^(โ1)โกใ((๐ฅ + 2)/3)+๐ถ2ใ Now, Putting values of I1 and I2 in (1) โซ1โใ(๐ฅ + 3)/โ(5 โ 4๐ฅ โ ๐ฅ^2 ).๐๐ฅ=(โ1)/( 2) โซ1โ(โ 2๐ฅ โ 4)/โ(5 โ 4๐ฅ โ ๐ฅ^2 )ใ+โซ1โ1/โ(5 โ 4๐ฅ โ ๐ฅ^2 ) ๐๐ฅ =โโ(5 โ 4๐ฅ โ ๐ฅ^2 )+๐ถ1+sin^(โ1)โก((๐ฅ + 2)/3)+๐ถ2 =โโ(๐ โ ๐๐ โ ๐^๐ )+ใ๐๐๐ใ^(โ๐)โกใ((๐ + ๐)/๐)+๐ชใ